2022
DOI: 10.1002/biof.1831
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant‐derived natural antioxidants in reduction of oxidative stress

Abstract: Free radicals are a group of damaging molecules produced during the normal metabolism of cells in the human body. Exposure to ultraviolet radiation, cigarette smoking, and other environmental pollutants enhances free radicals in the human body. The destructive effects of free radicals may also cause harm to membranes, enzymes, and DNA, leading to several human diseases such as cancer, atherosclerosis, malaria, coronavirus disease (COVID‐19), rheumatoid arthritis, and neurodegenerative illnesses. This process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(126 citation statements)
references
References 127 publications
4
75
0
Order By: Relevance
“…Though, experiments exhibited that TA can activate endogenous antioxidant molecules by boosting Cd removal, inhibiting NADPH oxidase, and modulating their upstream signaling pathways [ 14 , 38 ]. Accordingly, recent investigations found that TA improved antioxidant activity and scavenged free radicals [ 43 , 44 , 45 ]. It is well known that TA has two stabilized aromatic rings, with two hydroxyl groups (–OH) at the meta- and para- positions concerning one other [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though, experiments exhibited that TA can activate endogenous antioxidant molecules by boosting Cd removal, inhibiting NADPH oxidase, and modulating their upstream signaling pathways [ 14 , 38 ]. Accordingly, recent investigations found that TA improved antioxidant activity and scavenged free radicals [ 43 , 44 , 45 ]. It is well known that TA has two stabilized aromatic rings, with two hydroxyl groups (–OH) at the meta- and para- positions concerning one other [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bioactive compounds in medicinal plants causes the numerous biological effects such as antioxidant properties [8,9]. Natural antioxidants derived from medicinal plants are composed of polyphenols (including phenolic acids and flavonoids), carotenoids and vitamins [10]. These natural antioxidants are recognized for their ability to scavenge reactive oxygen species (ROS) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies support the use of antioxidant supplements in lowering oxidative stress and decreasing or preventing the development of disease-related consequences. Furthermore, by scavenging free radicals, antioxidants may aid in preventing diseases such as cancer, cardiovascular disease, Alzheimer's disease, and muscle degeneration (Akbari et al, 2022). The reducing power assay was first performed to explore the Fe 3+ to Fe 2+ transformation in the presence of T. asiatica ethyl acetate extract.…”
Section: Discussionmentioning
confidence: 99%